Study on landscape plants with colourful foliage - Khairani, binti Zaidan (Universiti Malaysia Sarawak (UNIMAS), 2005)
Colourful foliage plant is plant with coloured leaves: other than green colour Study of colourful foliage plant was carried out in University jvlalaysia Sarawak, around City of Kuching, Serian and Petrajaya. All specimens comprise of groundcover, shrub, alld trees.. Specimens were collected as much as founded at cerlain places. Furthermore, live-picture is taken and also simple propagation method is applied to each specimen; it is [0 see the propagation mode. All colourful foliage characteristics are described according to botanical methods, and preserved it as a herbarium sheet. While, live-picture is to illustrate the plants lookalike with it colourful [eaves. Moreover, it also to show the arrangement suitability of different plants toghether according to place and scenery. Simple propagation has completed to observe the propagation mode and whether it is easy-to-propagate. Therefore, this study is conducted as collaboration with landscape industry, at the S8mm lime as to support Malaysia government proposition due 10 Malaysia towards Garden City in 2005.